FcγR requirements and costimulatory capacity of Urelumab, Utomilumab, and Varlilumab - Leitner, Judith; Egerer, Ricarda; Waidhofer-Söllner, Petra; Grabmeier-Pfistershammer, Katharina; Steinberger, Peter (Frontiers in Immunology, 2023)
Targeting costimulatory receptors of the TNFR superfamily with agonistic antibodies is a promising approach in cancer immuno therapy. It is known that their efficacy strongly depends on FcR cross-linking. In this study, we made use of a Jurkat-based reporter platform to analyze the influence of individual FcRs on the costimulatory activity of the 41BB agonists, Urelumab and Utomilumab, and the CD27 agonist, Varlilumab. We found, that Urelumab (IgG4) can activate 41BB-NFB signaling without FcR cross-linking, but presence of the FcRs (CD32A, CD32B, CD64) augments the agonistic activity of Urelumab. The human IgG2 antibody Utomilumab exerts agonistic function only when crosslinked via CD32A and CD32B. The human IgG1 antibody Varlilumab showed strong agonistic activity with all FcRs tested. In addition, we analyzed the costimulatory effects of Urelumab, Utomilumab and Varlilumab in primary human PBMCs. Interestingly, we observed a very weak capacity of Varlilumab to enhance cytokine production and proliferation of CD4 and CD8 T cells. In the presence of Varlilumab the percentage of annexin V positive T cells was increased, indicating that this antibody mediated FcR-dependent cytotoxic effects. Collectively, our data underscore the importance to perform studies in reductionist systems as well as in primary PBMC samples to get a comprehensive understanding of the activity of costimulation agonists.